2004
DOI: 10.2307/4131473
|View full text |Cite
|
Sign up to set email alerts
|

Friendship and Advice Networks in the Context of Changing Professional Values

Abstract: In this article, I discuss the attributes of friendship and advice networks and hypothesize about their roles in maintaining and changing professional values. Advice networks sustain existing professional values in organizations. They are less likely to transmit new values because advice relations reflect current practice and may be negatively affected by changing values. Friendships rest on intimacy and trust rather than on existing task structures, so they can facilitate the development of new professional v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(94 citation statements)
references
References 53 publications
0
62
0
3
Order By: Relevance
“…Friendship and trust are closely related constructs, with friendship dependent on trust to grow, and trust often used as a conceptual base for friendship (Warris & Rafique, 2009). Friendships rest on intimacy and trust rather than on existing task structures and competences (Gibbons, 2004). Fang et al (2015) recently found that individuals' personality and their social network centrality are both positively associated with performance and career success.…”
Section: Centrality In Social Networkmentioning
confidence: 99%
“…Friendship and trust are closely related constructs, with friendship dependent on trust to grow, and trust often used as a conceptual base for friendship (Warris & Rafique, 2009). Friendships rest on intimacy and trust rather than on existing task structures and competences (Gibbons, 2004). Fang et al (2015) recently found that individuals' personality and their social network centrality are both positively associated with performance and career success.…”
Section: Centrality In Social Networkmentioning
confidence: 99%
“…Friendship networks affect individual and organizational well-being, yet we lack clear understanding of how they develop among professionals. Previous research has documented the importance of friendship ties for such internal operations of an organization as information sharing, decision making, and resource exchanges (e.g., Brass, 1984; Converse & Foa, 1993; Gibbons, 1996; Heimer, 1992; Krackhardt, 1992; Labianca, Brass & Gray, 1998; Lincoln & Miller, 1979), as well as for organizational outcomes (e.g., Krackhardt & Stern, 1988; Westphal, 1999) and interorganizational relationships (e.g., Allen, 1977; Bouty, 2000; Cook & Whitmeyer, 1992; Fichman & Goodman, 1996). Given the crucial roles of friendship in organizations, it seems equally critical that we develop greater understanding of dynamics in friendship networks among professionals.…”
mentioning
confidence: 99%
“…An advisor who provides support and advice throughout one’s career can be particularly beneficial for achieving long-term goals. Despite mounting evidence on the importance of having advisors (Gibbons, 2004; Sparrowe, Liden, Wayne, & Kraimer, 2001), little is known about how people select their advisors. We found that the predictions people make about which advisor characteristics they will rely on to make their decisions are often not used in practice.…”
Section: Discussionmentioning
confidence: 99%